Internal Audit Practices in State Universities: Evidence from Sri Lanka - Anojan, V. (University of Peradeniya, 2021)
The primary purpose of this study is to investigate the level of internal audit practices in the state universities of Sri Lanka. The researcher selected two high, middle, and bottom national and international-rank Sri Lankan state universities to find out significant mean differences regarding internal audit practices among the selected top, middle, and bottom rank state universities in Sri Lanka. The researcher used mean difference analysis; the t-test confirmed that there are no significant mean differences regarding internal audit practices among selected top, middle, and bottom-rank state universities in this study. Descriptive analysis shows that internal audit practices in state universities are below than moderate level in selected state universities in Sri Lanka.
Keywords: Internal Audit; Independent; Resources; Satisfaction; State Universities